ORAL MINOXIDIL EFFICACY AND SAFETY IN MALE ANDROGENETIC ALOPECIA - A LITERATURE REVIEW - Makarewicz, Maciej; Jałoszyński , Grzegorz; Marciniak , Oliwia; Konecki , Sebastian; Bylak , Natalia; Makowski , Bruno; Szczepański , Dawid; Gwizdek, Anna; Kurt, Maria; Gromadzki, Norbert; Barbachowski, Marcin Patryk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Low-dose oral minoxidil (LDOM) has emerged as a promising treatment for male androgenetic alopecia (AGA), offering potential advantages over topical formulations. This review evaluates the efficacy and safety of oral minoxidil for male AGA. Methods: A comprehensive literature search of PubMed, EMBASE, Cochrane Library, and Web of Science identified randomized controlled trials, observational studies, systematic reviews, meta-analyses, and consensus statements evaluating oral minoxidil (0.25-5 mg daily) for male AGA. Results: Across multiple studies, oral minoxidil demonstrated consistent efficacy for male AGA. Prospective studies reported increases in terminal hair density of 21.6-23.6% on the vertex with 5 mg daily dosing. Systematic reviews reported clinical response rates of 61-100%, with meta-analysis confirming that doses exceeding 1 mg were associated with greater efficacy. Approximately 35% of patients experienced significant symptom improvement and 47% showed improvement overall. Hypertrichosis was the most common adverse effect (15-49%), but rarely led to discontinuation (0.5%). Serious systemic adverse effects were infrequent: lightheadedness (1.7%), fluid retention (1.3%), and tachycardia (0.9%). No life-threatening events were reported, and only 1.7% discontinued treatment due to adverse effects. Meta-analysis confirmed that LDOM does not significantly affect blood pressure. Conclusions: LDOM is an effective and well-tolerated treatment for male AGA and represents a valuable option for patients preferring oral therapy or intolerant to topical treatment.